Characteristic expressions of GABA receptors and GABA producing/transporting molecules in rat kidney. - Kozue Takano (Public Library of Science (PLoS), 2014)
Gamma-aminobutyric acid (GABA) is an important neurotransmitter, but recent reports have revealed the expression of GABAergic components in peripheral, non-neural tissues. GABA administration induces natriuresis and lowers blood pressure, suggesting renal GABA targets. However, systematic evaluation of renal GABAergic components has not been reported. In this study, kidney cortices of Wistar-Kyoto rats (WKY) were used to assay for messenger RNAs of GABA-related molecules using RT-PCR. In WKY kidney cortex, GABAA receptor subunits, α1, β3, δ, ε and π, in addition to both types of GABAB receptors, R1 and R2, and GABAC receptor ρ1 and ρ2 subunit mRNAs were detected. Kidney cortex also expressed mRNAs of glutamate decarboxylase (GAD) 65, GAD67, 4-aminobutyrate aminotransferase and GABA transporter, GAT2. Western blot and/or immunohistochemistry were performed for those molecules detected by RT-PCR. By immunofluorescent observation, co-staining of α1, β3, and π subunits was observed mainly on the apical side of cortical tubules, and immunoblot of kidney protein precipitated with π subunit antibody revealed α1 and β3 subunit co-assembly. This is the first report of GABAA receptor π subunit in the kidney. In summary, unique set of GABA receptor subunits and subtypes were found in rat kidney cortex. As GABA producing enzymes, transporters and degrading enzyme were also detected, a possible existence of local renal GABAergic system with an autocrine/paracrine mechanism is suggested.